Analisis terhadap Penghentian Penyidikan pada Laporan Polisi Nomor: B.210/VIII/2018/JAMBI/SPKT”C” Tentang Tindak Pidana Pemerkosaan Anak - M Rudi Hartono; Lilis winantri (Wajah Hukum, 2020)
Law enforcement efforts by Law Enforcement Officers include a series of actions taken by police officers, Prosecutors, Judges, and Correctional Institutions. However, the spearhead in the handling of criminal cases that occur in the community is basically handled and carried out directly by police officers. In carrying out its duties, the Police have a basic duty as mandated in Article 13 of Law No. 2 of 2002 on the Police of the Republic of Indonesia, namely the Police have the task of maintaining security and public order, enforcing the law, and providing protection, protection, and service to the community. The task of law enforcement relates to the Criminal Justice System where the Police Department is one of its parts in addition to judges and prosecutors, which in the criminal justice system have the authority to make coercive efforts, which include the activities of arrest, detention, search and seizure. In carrying out the task of investigating the perpetrators of crimes or criminal cases, from the beginning of the investigation the case always coordinates with the Public Prosecutor, to avoid going back and forth on a recurring basis. In the police report Number: B.210/VIII/2018/Jambi/SPKT"C", there is a process of termination of investigation where the case of rape of a child is not continued to the stage of further law enforcement, namely the impeachment of the Prosecutor for prosecution, but in this case it is discontinued only to the level of investigation.